Sosialisasi Nomor Induk Berusaha untuk seluruh UMKM di Kelurahan Tanggung, Kota Blitar - Cantikasari, Sugma; Wahyu Ali Mashuri, Dandy; Ella Mustika, Elit; Atha Prakoso, Fauzan; Elvira Amanda, Gadis; Puspa Arum, Dewi (EDUPEDIA Publisher, 2022)
Over time, MSMEs in Kelurahan Tanggung have grown quite rapidly and each MSME has experienced improvements and development. The businesses undertaken by MSME actors in Kelurahan Tanggung vary from drum crafts, traditional yoyo toys, coconut fiber crafts, mushroom-based food preparations, catering, ginger syrup, and many more. In its development, the importance of a business license is because with licensing, business actors can show that the business being run does exist and is operating. By making a Business Identification Number (NIB), it is proof that business actors have a license to do business. NIB creation is integrated in the online single submission system (OSS). Therefore, KKN-T MBKM Wave II Group 29 UPNVJT students carried out socialization activities for NIB management in collaboration with DPMPTSP Blitar City. The method used is to record the types of MSMEs, document activities, and providePan understanding of thePimportance of having an NIB. The results obtained are an increase in understanding from MSME players in the Tanggung village in terms of the importance of having licenses.